Capacity Building For The Community of Nagari Andaleh, Batipuh Sub-District, Tanah Datar District, West Sumatra Province in Dealing Disasters, Flash Floods and Earthquakes: Peningkatan Kapasitas Masyarakat Nagari Andaleh Kecamatan Batipuh Kabupaten Tanah Datar Provinsi Sumatra Barat Dalam Menghadapi Bencana Banjir Bandang - Fauzan, Fauzan; Abdul Hakam; Febrin Anas Ismail; Andriani, Andriani; Yenny Narny; Riri Aprilia Putri (Universitas Lancang Kuning, 2025)
Increasing community capacity in dealing with natural disasters is a crucial step to reduce the risks and impacts caused by disasters. Nagari Andaleh, which is located in a disaster-prone area, especially in the West Sumatra region, often faces the threat of natural disasters that have the potential to damage social, economic and environmental life. This study aims to identify and develop strategies to increase the capacity of the Nagari Andaleh community in facing the flash floods disasters. With the holding of KKN-MBKM Disaster activities in Nagari Andaleh hosted by Andalas University, students and lecturers conducted socialization and in-depth surveys to the community, found an increase in community knowledge and awareness of disaster risks, as well as an increase in the ability to evacuate independently. Therefore, it is important to increase community capacity in order to reduce vulnerability and increase community resilience in the face of disasters that occur.